The Significance of Students’ Physical Activity for Their Engagement in Learning Activities During the Covid-19 Pandemic - Kemeryte-Ivanauskiene, Egle; Brandisauskiene, Agne; Cesnaviciene, Jurate; Daugirdiene, Ausra (Physical Education Theory and Methodology, 2022)
Study purpose. This study aims to clarify the extent to which students’ physical activity is significant for their engagement in the learning process. Materials and methods. The study sample was composed of 202 7th-10th grade students. The data collection was performed in May 2021. The research participants completed the anonymous questionnaire on an online platform. The standardized Physical Activity Questionnaire for Adolescents and the standardized Student Engagement Scale were used to assess levels of physical activity and affective and behavioural engagement. Results. The research findings showed that students’ physical activity depended on the time they participated in physical activities. The highest level of physical activity was during physical education classes. A statistically significant difference was determined in the boys’ and girls’ affective and behavioural engagement. The mean for the girls was higher than the mean for the boys. A statistically significant difference in the behavioural engagement of the 9th and 10th grade students was also found: 9th grade students were more engaged than 10th grade students. The multiple linear regression analysis demonstrated that gender (β = 0.332, p < 0.0001) and physical activity (β = 0.323, p < 0.0001) as predictors had a significant moderate effect on behavioural engagement. Conclusions. The research findings reveal that although the students’ physical activity was low during the COVID-19 pandemic period, this phenomenon (physical activity) still remains a predictor, which has a significant moderate effect on behavioural engagement. It was also determined that during the pandemic, the highest physical activity level of students depended mostly on obligatory physical education lessons. Thus, bearing in mind that physical education lessons were the main physical activity-enhancing measures, we would like to emphasise the importance of these lessons and their proper organisation.